Incorporating Paragraph Punch into EFL Writing Class - Asep Burhanudin (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2018)
This study aims at revealing the implementation of the use of video in teaching speaking skill. It involves twenty nine junior high school students, one English teacher, and two college students. The research method of this study is classroom action research (Kemmis and McTaggart 1988, cited in Burns, 2010) using observation and interview as data collection techniques. The gained data are then analyzed qualitatively. Findings present that the use of video can be beneficial for the teacher in teaching speaking skill, especially for the aspect of pronunciation (Stempleski, 1990, further discussed in Richards and Renandya, 2002). The results indicated that the students show improvements in their pronunciation after learning by using the video. In addition, the students are very enthusiastic in learning speaking by using video. The students focus on watching the video and most of them raise their hands to answer teacher’s questions related to the video. As the video provides the motion pictures which is more interesting for the students, the students focus on watching and trying to understand the content of the video. Based on these findings, it is recommended for the teachers to use video in teaching speaking skill at any school levels in order to make the students understand the lesson easily.